Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu Menggunakan Model PBL Kelas IV SD - Rahmi, Yunita; Zuryanty, Zuryanty (Universitas Negeri Padang, 2021)
This study aims to describe the improvement of student learning outcomes in integrated thematic learning using the Problem Based Learning Model in class IV of 15 Koto Tangah Elementary School, Agam Regency. This type of research is a classroom action research using qualitative and quantitative approaches. The research subjects were teachers and fourth grade students as many as 21 students. The results of the observation of the learning plan in the first cycle were 80.55%, and the second cycle was 94.44%. Teacher observations in cycle I were 78.12 and cycle II 93.75. While the improvement of student aspects in the first cycle was 82.81 and the second cycle was 93.75. While the average student learning outcomes in the knowledge aspect were 74.05 to 84.28, and in the skills aspect the average got 76.97 to 83.92. Keywords: problem based learning, learning outcomes, integrated thematic learning.